Dowling-Degos disease - A novel presentation of an uncommon disease - Prasenjeet Mohanty; Sonal Jain; Liza Mohapatra; Srikanta Acharya (Wolters Kluwer Medknow Publications, 2019)
Dowling-Degos Disease is a rare, pigmentary disorder with variable presentations. The most common among them are hyperpigmented macules and reticulate pigmentary anomaly of flexures. Many other phenotypic variations of Dowling-Degos disease have been reported in literature. We present here a case of Dowling-Degos disease with comedo-like lesions and pits without typical flexural hyperpigmented macules.